Comparing the Nutrient Management Pattern in Soybean and Rice based Cropping Systems by Soil Health Card holders and Non-holders - Meenal Dubey; Kallely C. Shinogi; H. K. Awasthi, M. A. Khan (Indian Journal of Extension Education, 2022)
The paper discusses about the importance of Soil Health Card (SHC) based nutrient management based on a study carried out during 2017-18 on 100 SHC beneficiary farmers and 50 SHC non-beneficiary farmers of Madhya Pradesh. Significant differences between the beneficiary and non-beneficiary farmers of soil health card in the nutrient use pattern in soybean and rice-based cropping systems were found. Majority of the SHC beneficiaries failed to adopt the fertilizer nutrients as per recommendation. Major reasons identified behind this negative trend were difficulty in understanding the SHC information without the help of an agricultural/ extension officer and lack of knowledge about the importance of SHC &benefits associated with adopting soil test based nutrient management. Further, the positive correlation of micro and secondary nutrients application with the yield and income from the adopters’ farm fields reaffirms the key role scientific nutrient management plays in improving agriculture based rural economies. More efforts from the promoting agencies required to convince farmers to adopt SHC based nutrient recommendation.